Legal developments in the W.T.O. - DAVEY, William J. (1996)
Reviews the four phases of dispute settlement in the WTO : consultation, panel proceeding, appeal, and implementation. Presents statistics of the dispute settlement experience 1995-96, and concludes that: (1) there will be greater use of the WTO dispute settlement system than there was of the GATT system; (2) there has been much greater use of the system by developing countries than in the past; (3) the WTO dispute settlement has been frequently used by the US, the European Communities and Japan, with the US being by far its major user; and, (4) it appeared initially that the new system might encourage parties to settle their disputes quickly, but it now appears that recourse to panels will become more common.